2018
DOI: 10.2147/cia.s157877
|View full text |Cite
|
Sign up to set email alerts
|

<em>Ginkgo biloba</em> extract EGb 761<sup>&reg;</sup> alleviates neurosensory symptoms in patients with dementia: a meta-analysis of treatment effects on tinnitus and dizziness in randomized, placebo-controlled trials

Abstract: BackgroundTinnitus and dizziness are frequent in old age and often seen as concomitant symptoms in patients with dementia. In earlier clinical trials, Ginkgo biloba extract EGb 761® was found to alleviate tinnitus and dizziness in elderly patients. Consequently, a meta-analysis was conducted to evaluate the effects of EGb 761® at a daily dose of 240 mg on tinnitus and dizziness associated with dementia.MethodsRandomized, placebo-controlled clinical trials of G. biloba extract EGb 761® identified by a systemati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 48 publications
0
34
0
1
Order By: Relevance
“…Notably, the exact 5 studies evaluated in this review for tinnitus and/or dizziness were previously identified and included in a meta-analysis reported by Spiegel et al (2018). Based on the Jarad scale assessment of methodological quality, the authors judged that the 5 studies included in their meta-analyses had a low bias risk [21]. Overall, they showed that GBE was superior to placebo, with weighted mean differences for [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, the exact 5 studies evaluated in this review for tinnitus and/or dizziness were previously identified and included in a meta-analysis reported by Spiegel et al (2018). Based on the Jarad scale assessment of methodological quality, the authors judged that the 5 studies included in their meta-analyses had a low bias risk [21]. Overall, they showed that GBE was superior to placebo, with weighted mean differences for [21].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the Jarad scale assessment of methodological quality, the authors judged that the 5 studies included in their meta-analyses had a low bias risk [21]. Overall, they showed that GBE was superior to placebo, with weighted mean differences for [21]. Interestingly, our review of the literature with regard to the effects of GBE in this indication (up to 1 January 2020) also failed to identify any additional RCTs that had been published in the last six years, i.e., since the RCT was published by Nikolova et al in 2013 [92].…”
Section: Discussionmentioning
confidence: 99%
“…Most of the studies on the EGb concern its neuroprotective effects, against ageing. Standardized Ginkgo biloba extracts (EGb) have been used for treatment and prevention of different neurological disorders as Alzheimer's disease [15,16], Parkinson's disease [17,18], cerebral vascular deficit, and dementia [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…Bioactive constituents extracted from Ginkgo biloba leaves such as flavonoids, their glycosides and terpene lactones, have attracted considerable attention in the therapy of Alzheimer's disease ( Janßen et al., 2010 ; Müller et al., 2019 ; Singh et al., 2019 ; Zeng et al., 2017 ), cognitive disorders ( Beck et al., 2016 ; Guan et al., 2018 ; Luo et al., 2018 ), cardiovascular disease ( Li et al., 2019 ; Nash and Shah, 2015 ; Tian et al., 2017 ; Wu et al., 2019 ) and cancer ( Bai et al., 2015 ; Liu et al., 2017 ; Park et al., 2016 ; Zhao et al., 2013 ). The pharmacology of individual constituents obtained from Ginkgo biloba leaves has been studied in preclinical and clinical trials ( Canter and Ernst, 2007 ; Ji et al., 2020 ; Savaskan et al., 2018 ; Spiegel et al., 2018 ; von Gunten et al., 2016 ). Flavonoids and trilactone terpenes are believed to be responsible for most of the pharmacological properties of Ginkgo biloba leaf extracts, and it has been suggested that synergistic effects might be of importance.…”
Section: Introductionmentioning
confidence: 99%